Impactos do Novo Código Florestal brasileiro nas áreas de vegetação protegida por lei na microbacia da Sanga Baitaca no Município de Marechal Cândido Rondon PR - Nascimento, Érica Vanessa Julião do (2015)
The new Brazilian Forest Code innovated when considering that the farm are size define the Environmental Protectected Areas (EPA) and the percentage of legal reserves, and not the width of the water bodies, as defined by the old law. This dissertation evaluated the impacto f change in Forest áreas in the Sanga Baitaca watershed, located in the municipality of Marechal Candido Rondon-PR, where small farms predominate. There were evaluated 36 properties, located around Sanga Baitaca. Of these, 48,08% were smaller than one fiscal module, 21,15% had between one and two fiscal modules. None of them had more than two fiscal modules. The data obtained show that the legally protected área decreased from 32,87% the total area sampled in the watershed for 2,32%, with the aplication of the new law. The largest reduction occurred in the legal reserves áreas, where the previous legislation provited a protection of 20% of the área of the watersed and this protection was completely eliminated, because all farms are smaller than four fiscal modules and none of them need to have legal reserves